the The Legal Politics of Executive–Legislative Power Relations in Post-Amendment Indonesia’s 1945 Constitution: The Legal Politics of Executive–Legislative Power Relations in Post-Amendment Indonesia’s 1945 Constitution - Aisyah Chairil; Maulana, Ramza Fatria; Dio Prasetyo Budi (Al-'Adl, 2025)
This study examines the dynamics of legal politics in the power relations between the executive and legislative branches in Indonesia following the amendments to the 1945 Constitution. The background to this study is the need to review Indonesia's constitutional structure, which was previously rife with executive dominance, particularly during the New Order era. The constitutional reforms undertaken between 1999 and 2002 were crucial in redesigning the state's power relations, with the aim of creating balance by strengthening the legislative, budgetary, and oversight functions of the House of Representatives (DPR). This research uses qualitative methods with a normative-juridical approach, anchored in the analysis of regulations, constitutional documents, and a review of primary and secondary legal literature. The results show that although the amendments have formally strengthened the DPR's position in the presidential system, their implementation has presented new challenges in the form of legislative dominance that is vulnerable to being exploited for partisan interests. The multiparty system in Indonesia's presidential system has also created power friction between the president and parliament, hampering government effectiveness. The chaos in the function of checks and balances is exacerbated by the weakness of countervailing institutions such as the Regional Representative Council (DPD) and the People's Consultative Assembly (MPR). Further reforms are needed that address not only institutional design but also the development of a deliberative political culture and the strengthening of independent oversight institutions to support substantive democracy